Mechanism of Muscle Vibrations During Stimulated and Voluntary Isometric Contractions of Mammalian Skeletal Muscle - Vaz, Marco Aurelio (1996)
When a muscle contracts it produces vibrations. The origin of these vibrations is not known in detail. The purpose of this study was to determine the mechanism associated with muscle vibrations. Mechanisms which have been proposed in the literature were described as theories (cross-bridge cycling, vibrating string and unfused motor unit theories). Specific predictions were derived from each theory, and tested in three conceptually different studies. In the first study, the influence of recruitment strategies of motor units (MUs) on the vibromyographic (VMG) signal was studied in the in-situ cat soleus using electrical stimulation of the soleus nerve. VMG signals increased with increasing recruitment and decreased with increasing firing rates of MUs. Similar results were obtained for the human rectus femoris (RF) muscle using percutaneous electrical stimulation of the femoral nerve. The influence of MU activation on muscle vibrations was studied in RF by analyzing VMG signals at different percentages (0-100%) of the maximal voluntary contraction (MVC). In our second study, we tested the effects of changing the material properties of the in-situ cat soleus (through muscle length changes) on the VMG signal. The magnitude of the VMG signal was higher for intermediate muscle lengths compared to the longest and the shortest muscle lengths. The decreased magnitude of the VMG signal at the longest and at the shortest muscle lengths was associated with increased passive stiffness and with decreased force transients during unfused contractions, respectively. In the third study, the effect of fatigue on muscle vibrations was studied in human RF and vastus lateralis (VL) musc1es during isometric voluntary contractions at a leveI of 70% MVC. A decrease in the VMG signal magnitude was observed in RF (presumably due to derecruitment of MUs) and an increase in VL (probably related to the enhancement of physiological tremor, which may have occurred predorninantly in a mediolateral direction) with fatigue. The unfused MU theory, which is based on the idea that force transients produced by MUs during unfused tetanic contraction is the mechanism for muscle vibrations, was supported by the results obtained in the above three studies.